Antibiotic Resistance Genes and Associated Phenotypes in Escherichia coli and Enterococcus from Cattle at Different Production Stages on a Dairy Farm in Central California - Saharuetai Jeamsripong; Xunde Li; Sharif S. Aly; Zhengchang Su; Richard V. Pereira; Edward R. Atwill (MDPI AG, 2021)
The objectives of this study were to characterize overall genomic antibiotic resistance profiles of fecal Escherichia coli and Enterococcus spp. from dairy cattle at different production stages using whole-genome sequencing and to determine the association between antimicrobial resistance (AMR) phenotypes and their corresponding genotypes. The Comprehensive Antibiotic Resistance Database (CARD) and ResFinder, two publicly available databases of antimicrobial resistance genes, were used to annotate isolates. Based on the ResFinder database, 27.5% and 20.0% of tested E. coli isolates (n = 40) harbored single and ≥3 antimicrobial resistance genes, respectively; for Enterococcus spp., we observed 87.8% and 8.2%, respectively. The highest prevalence of AMR genes in E. coli was for resistance to tetracycline (27.5%), followed by sulphonamide (22.5%) and aminoglycoside (20.0%); the predominant antimicrobial resistance genes in Enterococcus spp. targeted macrolide drugs (77.6%). Based on the CARD database, resistance to ≥3 antimicrobial classes was observed in all E. coli and 77.6% in Enterococcus spp. isolates. A high degree of agreement existed between the resistance phenotype and the presence of resistance genes for various antimicrobial classes for E. coli but much less so for isolates of Enterococcus. Consistent with prior work, fecal E. coli and Enterococcus spp. isolates from calves harbored a wide spectrum of resistance genes, compared to those from cattle at other production stages, based on the cross-sectional samples from the studied farm.